The History of Muslims and Christians in Papua: Tracing Cultural and Religious Heritage - Pamungkas, Cahyo (Center for Research and Development of Religious Literature and Heritage, 2014)
This is article derived from a thesis study in the Sociology Department of the University of Indonesia in 2008 exploring socio-economic, socio-political and socio-cultural contexts playing their roles in the formation of the political and religious fields along with their respective ”˜habitus’ of the social agents in the Papua land. This paper discusses the history of the term “papua” itself based on a historical study conducted by Solewijn Gelpke (1993). Based on historical approach, the relationship between Muslims and Christians in Papua can be traced as a religious and cultural heritage. Also, by using a sociological conception elaborated by Bourdieu (1992: 9), we may view the Papua land as a social space encompassing all conceptions of the social world. Bourdieu’s social space conception considers the social reality as a topology (Harker, 1990).